Comparative Results of Emergency Carotid Endarterectomy and Emergency Carotid Angioplasty With Stenting in the Acute Period of Ischemic Stroke. Multicenter Study Results - A. N. Kazantsev; V. A. Porkhanov; G. G. Khubulava; R. A. Vinogradov; V. N. Kravchuk; M. A. Chernyavsky; E. Y. Kachesov; A. A. Erofeyev; V. V. Matusevich; K. P. Chernykh; N. E. Zarkua; G. S. Bagdavadze; et al. (Неотложная медицинская помощь)
AIM OF STUDY Study of hospital results of emergency carotid endarterectomy (CEE) and carotid angioplasty with stenting (CAS) in the acute period of acute cerebrovascular accident (ACVA).MATERIAL AND METHODS From January 2008 to August 2020, the study included 615 patients with hemodynamically significant stenosis of the internal carotid arteries (ICA), operated on in the acute period of ischemic stroke (within 3 days from the onset of stroke). Depending on the type of revascularization implemented, all patients were divided into 2 groups: group 1 — CAS (n=312); 2nd group — CEE (n=357). Inclusion criteria were as follows: 1. Mild neurological disorders: NIHSS score 3–8; Modified Rankin Scale score 2 of less; Barthel Scale > 61; 2. Indications for CEE / CAS  according to the current national recommendations; 3. Ischemic focus in the brain not more than 2.5 cm in diameter. Exclusion criteria: 1. Presence of  con-traindications to CEE / CAS. Carotid angioplasty with stenting was performed according to the standard technique; in all cases, distal embolism  protection systems were used. Carot-id endarterectomy was performed  according to the classical and eversion techniques. When the retrograde pressure in the ICA was less than 60% of the systemic pressure, a temporary shunt (TS) was installed. In the postoperative period, all patients underwent multispiral computed tomography (MSCT) of the brain. In the absence of negative dynam-ics in the neurological status, MSCT was performed on the 7th day after the operation, if available, it was performed urgently. The checkpoints were the development of such unfa-vorable cardiovascular events as death, myocardial infarction (MI), stroke / transient is-chemic attack (TIA), “mute” stroke, “mute” hemorrhagic transformations, combinedend-point (death + all strokes / TIA + MI). Strokes were mute if diagnosed according to MSCT, without symptoms.RESULTS In 69% of diabetic patients with anterior myocardial infarction and in 63% of patients with posterolateral MI 12 months after PCI, signs of LV inferiority were revealed in the form of an increase in the indices of end-diastolic and systolic volumes of the LV and low ejection fraction (≤45%). In patients without diabetes, these figures were 18% and 31%, respectively. High concentrations of NT-proBNP on the first day of myocardial infarction after PCI were of the greatest value in the  diagnosis and prognosis of LV UR after 12 months.RESULTS When analyzing hospital complications, significant differences in the frequency of lethal outcome were not obtained (group 1: n=6 (1.92%); group 2: n=8 (2.24%); p=0.98; OR=0.85; 95% CI 0.29–2.49); MI (group 1: n=5 (1.6%); group 2: n=5 (1.4%); p=0.91; OR=1.14; 95% CI 0.32–3.99 ); ACVA (ischemic type) / TIA (group 1: n=5 (1.6%); group 2: n=6 (1.7%); p=0.82; OR=0.95; 95% CI 0.28–3.15), as well as “mute” ACVA (group 1: n=7 (2.2%);  group 2: n=15 (4.2%); p=0.23; OR=0.52; 95% CI 0.21–1.3). However, the vast majority of hemorrhagic transformations (group 1: n=2 (0.64%); group 2:  n=13 (3.6%); p=0.018; OR=0.17; 95% CI 0.03–0.76) and all “mute” hemorrhagic transformations (group 1: n=0; group 2: n=26 (7.3%); p=0.001;  OR=0.02; 95% CI 0.001–0.33) were observed only in the CEE group, which was reflected in the maximum values of the combined end point: group 1: n=22 (7.05%); group 2: n=73 (20.4%); p<0.0001; OR=0.29; 95% CI 0.17–0.48). Thus, in the CEE group, every 5th patient had a complication.CONCLUSION Carotid angioplasty with stenting is the safest method of revascularization for patients in the acute period of ACVA. This is largely due to the reduction in the risk of reperfusion syndrome and the prevention of embolism due to the use of modern protection systems. Carotid  endarterectomy can be performed with comparable efficiency only when a tempo-rary shunt is placed in the internal carotid arteries in the absence of unstable atheroscle-rotic plaque.